Break with tradition: understanding Namibia's relations with the Bretton-Woods international financial institution - Sakaria, Iipumbu (My University, 2009)
Abstract In 2003 the first President of the Republic of Namibia was relieved that Namibia had not taken a single penny from either the World Bank or the IMF3; as such, Namibia was one of the rare countries that had managed to do so since their independence. This scenario, unfortunately, came to an end in 2007 when Namibia officially requested a loan from the World Bank to start with the implementation of the ETSIP program4 and had thus broken its long and unusual record of not taking loans from the Bretton - Woods Institutions. This study, therefore, researched how and why Namibia stayed free from Bretton - Woods’ loans and why it eventually broke that tradition. The research found that Namibia had no economic crisis, whatsoever, warranting World Bank or IMF interventions; on the contrary, it strengthened a hypothesis advanced by Laila Smith5 suggesting that the World Bank uses its knowledge brokering role as a device to foster lending relationships with countries that initially refused to do so. The research therefore suggests that careful and informed engagement with the World Bank and IMF will be crucial if Namibia is to attain its developmental goals as outlined in its Vision 2030.